Program Beasiswa dan Peningkatan Kinerja Dampak Kepemimpinan, Kontribusi Sosial dan Ekonomi Alumni LPDP - Gufron, R Ery Bunyamin; Simanjuntak, Megawati; Novianti, Tanti (School of Business, Bogor Agricultural University (SB-IPB), 2022)
The Indonesia Endowment Funds for Education (LPDP) has an important role in supporting the government's vision to create superior human resources for advanced Indonesia through the provision of scholarship programs. However, so far, LPDP has not measured the impact (output) generated by the alumni of the scholarship recipients. This study further aims to analyze how the LPDP scholarship program can affect the improvement of leadership aspects and social and economic contributions of the recipients. This study involved a sample of 388 LPDP scholarship recipients both from within and outside the country, who were selected through the stratified random sampling method. The collected data was then analyzed using PLS-SEM (Partial Square Least-Structural Equation Modeling) analysis. The results of the study show that the scholarship program is able to positively and significantly improve aspects of the leadership, social and economic contributions of alumni who are recipients of the LPDP scholarship program. Thus, the LPDP institution can increase the output generated from its alumni by optimizing the scholarship program through evaluation of the debriefing preparation program (PK), the establishment of empowerment and talent pooling programs, as well as increasing the intensity of cooperation (synergy) between LPDP recipient alumni organizations. Keywords: alumni, scholarship,impact, LPDP, SEM PLS